Lie and Jordan structures of differentially semiprime rings - Artemovych, O.D.; Lukashenko, M.P. (Algebra and Discrete Mathematics, 2015)
Properties of Lie and Jordan rings (denoted respectively by RL and RJ) associated with an associative ring R are discussed. Results on connections between the differentially simplicity (respectively primeness, semiprimeness) of R, RL and RJ are obtained.